Investigation of Higher Education Students' Interest in Sports and Usage Levels of University Sports Facilities - Serdar Ceyhun (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction The size, number, capacity, characteristics and quality of the areas where sports activities can be carried out in universities are among the leading indicators of student investment.